Perceptions of barriers and facilitators to opioid reduction after total joint arthroplasty among orthopedic surgeons practicing in Canada, Japan, and the Netherlands: A qualitative description study - Mansi Patel; Parsia Parnian; Kim Madden; Sheila Sprague; Anita Acai; Ydo Kleinlugtenbelt; Natsumi Saka; Ellie Landman; Harsha Shanthanna; Vickas Khanna; Jason W. Busse (PLoS ONE, 2025)
Opioid analgesics are commonly prescribed after total knee and hip arthroplasty to manage pain. Rates of opioid prescribing after arthroplasty differ by country, suggesting differences in policies or surgeons’ practices. We adopted a qualitative description design to explore and compare Canadian, Dutch, and Japanese orthopaedic surgeons’ perceptions of facilitators and barriers to opioid reduction after total joint arthroplasty. We used a combination of convenience and purposive sampling, and snowball recruitment to facilitate 27 semi-structured interviews online or via a phone call. We concurrently collected and analyzed data using conventional (inductive) content analysis. In our sample, all Canadian surgeons and almost all Dutch surgeons prescribed opioids to all arthroplasty patients post-discharge. Surgeons in Japan showed much greater variability, with half of those interviewed prescribing opioids to only a minority or no patients post-discharge. Japanese surgeons indicated that a 10–30-day hospital stay was typical after surgery and believed that opioids were often unnecessary for managing postoperative pain. Dutch surgeons described using an institutional standard pain management protocol, while Canadian and Japanese surgeons noted high variability in the type and dose of opioids prescribed, even within the same institution. Orthopaedic surgeons in each country identified challenges and facilitators to reduced postoperative opioid use in six key areas: (1) opioid prescribing practices, (2) patient factors, (3) collaborative care, (4) opioid prescribing policies/guidelines, (5) surgeon education, and (6) personal perceptions/beliefs. Canadian, Dutch, and Japanese orthopedic surgeons in our study described a range of individual, patient, and system level contributors to variability in opioid prescribing after joint replacement surgery. These findings suggest that multifactorial and context-specific approaches may be required to address barriers and optimize postoperative use of opioids.